Síndrome do climatério - Fernandes, César Eduardo; Stephan, Cristina [UNESP]; Nasser, Elizabeth Jehá; De Souza Ferreira, José Arnaldo; De Melo, Nilson Roberto; Peixoto, Sérgio (My University, 2005)
The climateric is characterized by progressive hipoestrogenism and by tissue and functional alterations that leads the women to aging. The diagnosis approach needs to consider the symptoms originated by estrogenic deficiency and by the more prevalent chronic diseases in this lifetime, for instance, among others, the cardiovascular and osteoporosis diseases, witch need a systematic screening. The therapeutic management must consider the proposition of healthy life habits and, when indicated, pharmacological treatment for estrogenic deficiency or for anothers comorbidities existent. The estroprogestative hormonal therapeutic is a valuable tool to provide health and better quality of life, once obeyed the individualized criterion of the cases, doses, hormonal composition and mainly of the opportunity of intervention. There are nonhormonal alternatives to treat the menopausal symptoms, as the antidepressives and phytoestrogens. It's also advised to combine with regular physical activities and adequate calcium intake. © Copyright Moreira Jr. Editora. Todos os direitos reservados.
Climateric syndrome
Keywords: Climateric; Hormone replacement therapy; Menopause; algestone; calcitriol; calcium; conjugated estrogen; cyproterone acetate; drospirenone; estradiol; estradiol valerate; estriol; estrogen; fluoxetine; gestodene; medroxyprogesterone acetate; norethisterone acetate; norgestimate; paroxetine; phytoestrogen; progesterone; promestriene; serotonin uptake inhibitor; testosterone; testosterone undecanoate; tibolone; trimegestone; aging; calcium intake; cardiovascular disease; chronic disease; comorbidity; diagnostic approach route; estrogen deficiency; female; human; menopausal syndrome; osteoporosis; physical activity; prevalence; quality of life; review; screening; symptomatology